Exploring IoT User Dimensions: A Multi-case Study on User Interactions in ‘Internet of Things’ Systems - Olsson, Helena H.; Bosch, Jan; Katumba, Brian (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2016)
‘Internet of Things’ (IoT) systems are fundamentally changing the way in which users interact and perceive technology. In this paper, we focus on two of the numerous dimensions of IoT systems with which the users interact; (1) the IoT user interface and (2) the IoT ecosystem. Based on literature, we develop a model that identifies how data is presented to users and how users interact with the system, and the level at which systems interconnect with, and collects data from, multiple systems. Companies can use the model to assess their systems in order to identify the current state of their systems and to identify the desired state. Moreover, the model can be used to better understand the steps necessary for transforming from one dimension to another in order to develop more advanced IoT systems.